2019
DOI: 10.1097/shk.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

Budding Uninhibited by Benzimidazole-1 Insufficiency Prevents Acute Renal Failure in Severe Sepsis by Maintaining Anticoagulant Functions of Vascular Endothelial Cells

Abstract: Severe sepsis is critical to health and can result in acute renal failure (ARF). Tissue factor (TF) and thrombomodulin (TM) play key roles in vascular endothelial functions by helping maintain microcirculation in the kidney. Budding uninhibited by benzimidazole-1 (Bub1) plays a role in Akt and JNK signaling, which control TF and TM, respectively. We hypothesized that Bub1 could control vascular endothelial function in sepsis. The aim of this study was to determine the role of Bub1 in septic ARF. We used Mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…What’s more, it was reported that AURKA has associated with CRC liver metastasis (CRLCM) ( 26 , 27 ). Budding uninhibited by benzimidazoles ( BUB1 ) is also a member of the serine/threonine-protein kinase family ( 28 ). Over 90 percentages of all human solid tumors have a common feature that mutations occur in the spindle checkpoints ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, it was reported that AURKA has associated with CRC liver metastasis (CRLCM) ( 26 , 27 ). Budding uninhibited by benzimidazoles ( BUB1 ) is also a member of the serine/threonine-protein kinase family ( 28 ). Over 90 percentages of all human solid tumors have a common feature that mutations occur in the spindle checkpoints ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, under pathological conditions, the CEC count can rise markedly [24]. TM and vWF are also key markers used in monitoring endothelial injury [2527]. Wu et al reported that miR-26a can inhibit PFKFB3 in a targeted manner, thereby reducing VEC injury caused by lower-extremity ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…We found 29 papers that used this antibody to measure human, mouse, rabbit and canine TF by a variety of methods, including 15 that used the antibody for western blotting (Table S1). 33‐61 Importantly, Abcam evaluated the ability of the antibody to detect human TF in wild‐type and KO cell lines by western blotting 62 . Based on the data they obtained, they recently withdrew ab151748 and stated that “after evaluation, using a HAP1 knockout cell line, ab151748 was not shown to react specifically with the target protein and has therefore been discontinued.” We confirmed that this antibody does not detect mouse TF by western blotting but rather a nonspecific band.…”
Section: Discussionmentioning
confidence: 99%